Student Assessment of Quality of Access at the National Open University of Nigeria (NOUN) - Juliet O. Inegbedion; Folorunso I. Adu; Christine Y. Ofulue (Open Praxis, 2016)
This paper presents a study conducted by Inegbedion, Adu and Ofulue from the National Open University of Nigeria. The study focused on the quality of access (admission and registration) at NOUN from a student perspective. A survey design was used for the study while a multi-stage sampling technique was used to select the sample size. All the 78,555 registered students in all the 61 Study Centres of the University at the time of the study formed the population; out of which 3,060 students were sampled. The questionnaire instrument is the Institutional Internal QA Tools and Instrument developed by the African Council for Distance Education (ACDE) as a regulatory mechanism. The data collected were analyzed using simple statistics. The result showed that 66% of the students confirmed that NOUN has published clear policies on the admission and registration of students. About 29.1% of the students were not satisfied with the transparency of the admission process. In conclusion, the study revealed high quality of access and some deficiencies in website and Internet connectivity.